Perlindungan Hukum Atas Klaim Kain Tenun Sumba Timur Sebagai Motif Seni Wilayah Lain - Sherine Aurellia Untono (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2025)
This journal raises a case regarding the actions and implementation of a fashion show conducted by SMK NU Banat Kudus and 2 (two) students named Fitria Nooraisyah (19) and Farah Aurelia Majid (17) at the Fashion Show "La Mode" Sur La Seine a Paris in Paris in 2019 which did not fulfill the statutory provisions, namely Article 38 of the UUHC, Article 40 letter j of the UUHC, Article 4 paragraph (1) of the Ministerial Regulation and Human Rights Number 13 of 2017 concerning Communal Intellectual Property Data, and violating Article 1365 of the Civil Code which resulted in unlawful actions. Article 33 of Government Regulation No. 56 of 2022 concerning Communal Intellectual Property, and violating article 1365 of the Civil Code which results in unlawful acts. The non-fulfillment of the statutory provisions is because SMK NU Banat kudus and the two students violated article 38 of the UUHC because they had participated in a fashion show with a horse-patterned East Sumba ikat woven fabric (njara) and claimed that the woven fabric belonged to the jepara district called troso nimbrung. Keyword: Communal, violation, fashion, njara